Changing Professional Behaviors in the Digital World Using the Medical Education E-professionalism (MEeP) Framework—a Mixed Methods Multicentre Study - Shaista Salman Guraya; Muhamad Saiful Bahri Yusoff; Fiza Rashid-Doubell; Denis W. Harkin; Suhail H. Al-Amad; Salim Fredericks; Mouhammad Omar O. Halabi; Hatem Moussa; Saad Imad Yousef Mallah; Jessica Atef Nassef Sefen; Heba Khalid A. Rahman Mohamed Ishaq AlKoheji; Manal Ebrahim Ali Althawadi; et al. (Frontiers Media S.A., 2024)
Volume 9